The Development of Regional Communist Elites in the Czech Lands 1945–1956 - Bily, Matej; Lozi, Marian; Slouf, Jakub (Pamięć i Sprawiedliwość, 2018)
The focus of the study is the analysis of the elite at the regional and departmental levels of the Communist Party of Czechoslovakia (CPC) in the period 1945–1956. Specifically, it deals with the holders of the administratively, most important function, that of political or later head secretary. However, it also respects an actual state of affairs within studied regions and departments and designates elite accordingly. Through methods of prosopography it examines social background of the selected elite and how these performed dominance in their respective domains. It comes to the conclusion that within the concerned period the social origins and power practices of the elite shifted dramatically in accordance with the transformations of the Czechoslovak state-socialist dictatorship itself. These changes did not happen continuously, but in conditions of strained hardships and major turnarounds. In the process, new or semi-new elite was created and revolutionary ethos gave way to stabilization and smooth performance of power.